2020
DOI: 10.9734/ajriz/2020/v3i330092
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Ticks Infestation of Dogs in Runjin Sambo Area of Sokoto, Sokoto State, Nigeria

Abstract: Ticks are still considered a major cause of zoonotic diseases most especially to dogs and other related animals. This study was conducted to assess the ticks infestation of dogs in Runjin Sambo area Sokoto. The sample was collected using hand picking and hair brushing method with the assistance of dog owners. A total of sixty dogs were randomly selected in four different sub areas in Runjin Sambo. The locality, sex and age of the dogs were noted. The ticks species were identified in the entomology laboratory u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Workers from abroad such as Hadi et al (2016) [7] from Indonesia also recorded higher prevalence in male than female dogs. On contrary Chander et al (2020) [4] from Bikaner, Rajasthan reported higher prevalence in female dogs (68%) than in male dogs (32%) and Lema et al (2020) [16] from Nigeria also revealed prevalence rate was in males (31.67%) and the females (43.33%). The significantly higher proportion of ectoparasitic infestation in male may be due to hormonal factors which predispose male dog more susceptible to ectoparasite infection (Sahu et al, 2013) [23] .…”
Section: Sex-wise Prevalence Of Ectoparasite Infestation In Dogsmentioning
confidence: 92%
See 1 more Smart Citation
“…Workers from abroad such as Hadi et al (2016) [7] from Indonesia also recorded higher prevalence in male than female dogs. On contrary Chander et al (2020) [4] from Bikaner, Rajasthan reported higher prevalence in female dogs (68%) than in male dogs (32%) and Lema et al (2020) [16] from Nigeria also revealed prevalence rate was in males (31.67%) and the females (43.33%). The significantly higher proportion of ectoparasitic infestation in male may be due to hormonal factors which predispose male dog more susceptible to ectoparasite infection (Sahu et al, 2013) [23] .…”
Section: Sex-wise Prevalence Of Ectoparasite Infestation In Dogsmentioning
confidence: 92%
“…According to Sahu et al (2013) [23] , Rhipicephalus sanguineus is the most frequent species of tick to parasitize dogs in India, followed by Rhipicephalus haemaphysaloides, Rhipicephalus microplus, Haemaphysalis longicornis, and Haemaphysalis bispinosa (Augustine et al, 2017) [3] . Ticks can spread bacteria, rickettsiae, viruses, and protozoa, including tick-borne encephalitis, Rocky Mountain spotted fever, Lyme disease, tularemia, Q fever, Babesiosis, Hepatozoonosis (Lema, 2020) [16] . Dogs typically have fleas of the species Ctenocephalides canis, Ctenocephalides felis, Pulexirritans, and Echidnophaga gallinacea (from poultry), which are considered to be moderately specific (Wall and Shearer, 2001) [30] .…”
Section: Introductionmentioning
confidence: 99%